Geoquímica e geocronologia U-Pb (SHRIMP) de granitos da região de Peixoto de Azevedo – província aurífera de Alta Floresta – MT - Silva, Fernanda Rodrigues da (2014)
The analysis of petrographic, geochemical and geochronological data of granites in the region of Peixoto de Azevedo - MT, in the eastern portion of the Alta Floresta Gold Province, led to the recognition of two granitic bodies bounded by major faults and shear zones in the region. In the northwestern portion, a body with dimensions of approximately 50 km ², featured as biotite granodiorite , coarse-grained , porphyritic texture inequigranular to, metaluminous to peraluminous, calc- alkaline high potassium and magnesium occurs. In the southeastern portion of the area, a body with approximately 100 Km ², featured as biotite monzogranite, coarse-grained, equigranular to porphyritic texture, slightly peraluminous, calc- alkaline high potassium and occurs dominantly ferrous character. U- Pb dating ( SHRIMP zircon ) in this work showed that the biotite monzogranite has an age of 1869 ± 10 Ma, which allowed to include it as part of Intrusive Suite Matupá, while the biotite granodiorite had age 1761 ± 12 Ma, cronocorrelata age Intrusive Suite Teles Pires. However due to compositional variations, remained for the designation of granodiorite Granite Peixoto. Both units show patterns of Rare Earth Elements with enrichment of light over heavy and negative Eu anomaly ( Lan / YBN  7.6 to 17.31 and ratios Eu / Eu * between 0.46 to 0.72 for biotite monzogranite and Lan / YBN  7.13 to 29.09 with ratios Eu / Eu * between 0.25-0.40 for the biotite granodiorite ). Trace elements for both present negative anomalies of Ba, P, Ti and Nb indicating an evolution for mineral fractionation where there is involvement of plagioclase, apatite and titanite and ilmenite or where the negative Nb anomaly is related to inheritance subductadas plates. Two hypotheses are suggested to the granites of the region. The first assumes that the magmatic arc called Juruena, begins with the formation of granites Intrusive Suite Matupá (1870 Ma ) and continues until the age of granodiorite Peixoto ( 1761 Ma ). The compositional variation generated in the period from 1870 Ma to 1761 Ma is justified by the presence of a heterogeneous crust reworked during subductio. The second hypothesis considers that only the monzogranite was generated in active continental margin environment, in a mature stage. The granodiorite probably would have originated in post -collisional stage, as a result of fusion of delaminated lithospheric plate , followed by crustal contamination. The first hypothesis are based upon the absence of evidence for collisional zones in the region. However in case 2, it is considered that the absence of collisional signatures may be related to the low rate of crustal exhumation or the lack of geological studies.